Towards a biolinguistic understanding of grammar : essays on Interfaces - Di Sciullo, Anne-Marie, 1951- (Linguistik aktuell ;, 2012)
The theoretical proposals brought forward in this book as well as the results from the reported experimental studies present genuine contributions to the biolinguistic program. The papers contribute to our understanding of the properties of the computations and the representations derived by the language faculty, viewed as an organism of human biological. Towards a Biolinguistic Understanding of Grammar: Essays on Interfaces adds to the usual notion of interfaces, which is generally understood as the connection between syntax and the semantic system, between phonology and the sensorimotor syst.